The people, and uncollected stories - Malamud, Bernard; Giroux, Robert (New York : Farrar, Straus, Giroux, 1989)
Presents Bernard Malamud's final unfinished manuscript, "The People," about a Jewish peddler who takes on all the sufferings of a Pacific Northwest Indian tribe after being adopted as their chief; and includes sixteen uncollected stories.
Adult
Keywords: Short stories